Analysis of Language Variation: A Sociolinguistic Review of Functions, Types, and Forming Factors in Society - Istiana (Konsultan Jurnal Ilmiah Indonesia, 2025)
This article is a sociolinguistic review that aims to comprehensively analyze language variation, including its functions, types, and shaping factors in society. Language is understood to be inseparable from the social context of its users, where the phenomenon of differences in language styles influenced by social factors gives rise to the concept of language variation. Language variation arises because the community of speakers is diverse in terms of age, education, occupation, social status, and communication situations. This study identifies various types of language variation such as regional variation (dialect), social variation, functional variation (register), variation in formality (style), variation in means (spoken and written), and individual variation (idiolect). Furthermore, this study summarizes the functions of language variation, including communicative, social identity, solidarity/intimacy, aesthetic, persuasive, emotional, and practical functions. Factors shaping variation are discussed, including geographical, social, situational/contextual, functional/field, individual, cultural/group, as well as developments in time and technology. The conclusion of this review shows that language variation is a natural phenomenon that not only enriches the treasury of communication but also reflects the identity, solidarity, and dynamics of society. A good understanding of language variation is crucial for fostering tolerance for linguistic diversity and improving effective communication skills in various social contexts.